Physical characterization of freeze-dried foam prepared from Aloe vera gel and guar gum - SANTACRUZ-VÁZQUEZ, Verónica; SANTACRUZ-VÁZQUEZ, Claudia; LAGUNA-CORTÉS, José Oscar (Vitae, 2015)
Background: Foams are colloidal dispersions of a gas suspended in a dispersing phase, which consisting of a semi-freeze-dried or viscous liquid phase. The physical properties of food foams are the result of the bubble characteristics and their spatial arrangement. Objectives: The aim of this work was to obtain foams of A. vera gel and guar gum and describe the changes in their physical properties and microstructure during freeze-drying using the fractal dimension concept and image analysis techniques. Methods: The porosity, density, and volume expansion factor of the fresh foams that were based on the A. vera foams were determined. The kinetics of foam texture, color, porosity and microstructure of the freeze-dried foams were obtained. The fractal texture dimension of surface (FDSDBC) and microstructure (FDESEM) of the foams were determined as indicators of structural changes after freeze-drying. The guar gum concentrations used to obtain the A. vera prefoam were expressed in w/w as F1 (control simple without gum), F2 (2%), F3 (4%) and F4 (6%). Results: We obtained stable freeze-dried foams of Aloe vera gel and guar gum. The porosity, density and volume expansion factor of the fresh and freeze-dried foams were affected by the addition of the guar gum. Changes in the topology of the freeze-dried foam surface during the drying process resulted in a high rugosity compared with the original smooth surface. The microstructure of the dried foam samples suggested a relationship between the gum concentration of the prefoam A. vera gel mixture and the physical properties before and after freeze-drying, such as an increase in the microstructural alterations and surface roughness during freeze-drying. The roughness of the freeze-dried foam surface, described by the FDSDBC represented the macroscopic physical changes of the samples and correlated with the changes in the foam microstructure, which were described by the fractal dimension of the Environmental Scanning Electron Microscopy ESEM microphotographs (FDESEM). Conclusions: The digital analysis of the structure and porosity of the freeze-dried foam can be used to quantify the effect of gum concentrations on the morphological features and physical properties of foams during freeze-drying.